KAJIAN TEOLOGIS-PRAKTIS TENTANG DOA PUASA MENURUT KITAB ESTER 4:1-17 DAN IMPLIKASINYA BAGI ORANG PERCAYA - Febe Seatle Ernawaty; Sutikto; Nelly (Phronesis: Jurnal Teologi dan Misi, 2023)
The fasting prayer in the Book of Esther has not been studied seriously in Indonesia. On the one hand, prayer and fasting are central practices for every believer. On the other hand, some churches seem to be increasingly ignoring the teaching of fasting prayer to believers. This study wants to respond to theological and practical problems in the Indonesian context, although the book of Esther is not the only book that records people praying and fasting. However, this research highlights the implications it could have for modern believers. This research applies literature study using qualitative methods. This research shows that God acted appropriately following Esther's faith, which removed doubts and worries. Fasting prayer became a means for Esther to strengthen her faith in facing the problems.